Autophagy in Current Trends in Cellular Physiology and Pathology 2016
DOI: 10.5772/64534
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Non-Alcoholic Fatty Liver Disease (NAFLD)

Abstract: Abstract"utophagy is a mechanism involved in cellular homeostasis under basal and stressed conditions delivering cytoplasmic content to the lysosomes for degradation to macronutrients. The potential role of autophagy in disease is increasingly recognised and investigated. To date, a key role of autophagy in hepatic lipid metabolism is recognised and dysfunctional autophagy might be an underlying cause of non-alcoholic faty liver disease N"FLD . Nevertheless, the exact role of autophagy in lipid metabolism rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…The key role of autophagy in hepatic lipid degradation in various cell types, including adipocytes and hepatocytes, and in dysfunctional autophagy might lead to the accumulation of lipids and TGs (Kwanten et al, 2016). The upregulation of AMPK and downregulation of mTOR observed in the present study may have induced autophagy.…”
Section: Discussionmentioning
confidence: 51%
“…The key role of autophagy in hepatic lipid degradation in various cell types, including adipocytes and hepatocytes, and in dysfunctional autophagy might lead to the accumulation of lipids and TGs (Kwanten et al, 2016). The upregulation of AMPK and downregulation of mTOR observed in the present study may have induced autophagy.…”
Section: Discussionmentioning
confidence: 51%
“…Ultramicrostructural analysis also revealed that HFD inhibits hepatic autophagy but OCN reversed the effect. Autophagy, a self-degradative process, is a critical biological function for the degradation of damaged intracellular components by lysosomes ( Amir and Czaja, 2011 ; Ni et al., 2012 ; Kwanten et al., 2016 ; Mao et al., 2016 ). Hepatocytes' autophagic function is affected by hepatocytic lipid accumulation by which it reduces the infusion efficiency between autophagosomes and lysosomes, leading to suppressed autophagy ( Singh et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes' autophagic function is affected by hepatocytic lipid accumulation by which it reduces the infusion efficiency between autophagosomes and lysosomes, leading to suppressed autophagy ( Singh et al., 2009 ). The hepatocytes' autophagy is also inhibited by insulin resistance-associated hepatocyte oxidative stress, inflammatory reaction, and apoptosis ( Amir and Czaja, 2011 ; Kwanten et al., 2016 ; Wu et al., 2018 ). Autophagy has been potentially linked to fibrogenesis ( Amir and Czaja, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with in-depth study of autophagy, several studies have found that abnormality of autophagy function is closely related to diabetic liver injury. 4,35,36 Autophagy may be involved in the occurrence and development of diabetic liver injury through degradation of lipid droplets, 37−39 attenuation of insulin resistance, 40,41 and maintenance of pancreatic islet beta cell structure and function. 42,43 Furthermore, increased autophagy can improve NAFLD animal models of hepatic steatosis and reduce chronic liver injury.…”
Section: ■ Discussionmentioning
confidence: 99%